2011
DOI: 10.1093/eurjhf/hfq213
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular side effects of cancer therapies: a position statement from the Heart Failure Association of the European Society of Cardiology

Abstract: The reductions in mortality and morbidity being achieved among cancer patients with current therapies represent a major achievement. However, given their mechanisms of action, many anti-cancer agents may have significant potential for cardiovascular side effects, including the induction of heart failure. The magnitude of this problem remains unclear and is not readily apparent from current clinical trials of emerging targeted agents, which generally under-represent older patients and those with significant co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
278
1
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(312 citation statements)
references
References 64 publications
2
278
1
19
Order By: Relevance
“…In this model, anthracyclines activate cardiac stress pathways through several mechanisms that include generation of reactive oxygen species and oxidative damage of cardiomyocytes,66 and inhibition of topoisomerase 2β leading to double‐stranded breaks in DNA 67. Concomitant ErbB2 inhibition disrupts cardioprotective and prosurvival signaling, diminishing the heart's ability to tolerate noxious stimuli and recover 68, 69, 70, 71. Indeed, preclinical studies showed that activation of ErbB2 by recombinant neuregulin‐1 protected cardiomyocytes from the myofibrillar disarray caused by anthracyclines,72 whereas administration of an ErbB2 antibody increased susceptibility of myofilaments to doxorubicin 73…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, anthracyclines activate cardiac stress pathways through several mechanisms that include generation of reactive oxygen species and oxidative damage of cardiomyocytes,66 and inhibition of topoisomerase 2β leading to double‐stranded breaks in DNA 67. Concomitant ErbB2 inhibition disrupts cardioprotective and prosurvival signaling, diminishing the heart's ability to tolerate noxious stimuli and recover 68, 69, 70, 71. Indeed, preclinical studies showed that activation of ErbB2 by recombinant neuregulin‐1 protected cardiomyocytes from the myofibrillar disarray caused by anthracyclines,72 whereas administration of an ErbB2 antibody increased susceptibility of myofilaments to doxorubicin 73…”
Section: Pathophysiologymentioning
confidence: 99%
“…Although several guideline groups, including the American Society of Echocardiography, the American Society of Clinical Oncology, the Heart Failure Association of the European Society of Cardiology (ESC), the European Society of Cardiology, and the European Society of Medical Oncology, have published recommendations and consensus statements for the diagnosis and management of cardiotoxicity from cancer therapies17, 20, 53, 68, 77 no widely accepted international guidelines are available. In the United States, neither the American Heart Association nor the American College of Cardiology have published specific recommendations.…”
Section: Recommendationsmentioning
confidence: 99%
“…Before treatment initiation, cardiovascular risk assessment is required. Cardiovascular risk factors should be aggressively treated 2 and if cardiotoxicity remains a great concern, an alternative chemotherapeutic regimen with less known cardiotoxicity should be found. Patients must be monitored during and after chemotherapy -late-onset left ventricular dysfunction should always be suspected along their lives 1,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Their cardiotoxicity is irreversible, cumulative, dose-dependent and it's due to direct lesion/loss of myocites. Heart Failure (HF) can present acutely with high doses but it is most frequently a late-onset complication 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to identify cancer patients in the early stages of heart disease (stage A: high risk for heart failure without structural heart disease of symptoms; stage B: structural heart disease without signs or symptoms of heart failure) so that earlier intervention and close monitoring can be instituted 13 . Cancer patients with cardiovascular risk factors undergoing systemic therapy require a multidisciplinary approach that optimizes the balance between their cancer treatment outcome and cardiac health: "The cured cancer patient of today does not want to become the heart failure patient of tomorrow" 14 .…”
Section: Cardiac Toxicity: View Of a Cardiologistmentioning
confidence: 99%